TELEMEDICINE: DIFFUSION OF HEALTH COMMUNICATION - Yunidyawati Azlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The period of the Covid-19 pandemic demanded the Government to limit social activities or what is known as PSBB to the public. Including urging the public to postpone visits to the hospital. As a substitute, the Government implemented the telemedicine concept, namely the concept of long-distance treatment so that people could continue to consult their health problems without having to come to the hospital. The research method used is qualitative - descriptive by means of observation and literature study. Then analyzed descriptively by describing the results of the study in the form of a qualitative research report.